PENGARUH METODE DISCOVERY-INQUIRY TERHADAP PROFIL KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN TOPIK KELARUTAN - Fina Khaerunnisa Frima (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2020)
The era of industrial revolution 4.0 contributes major challenges in 21st century of education in obtaining qualified students. Education process lead to the development of student skills and attitudes in addition to the knowledge learning process. Critical thinking skills (KBKr) is one of the 21st century learning skills that students should have and needs to be practiced during learning process in school. One of the learning method to practice KBKr is discovery-inquiry learning method. The purpose of this study is obtain the affect of discovery-inquiry learning method on student’s critical thinking skill achievement in topic of solubility. Method of research is pre-experimental and one-shot case study as the design of method research. Subjects were 41 students at one of the senior high school in Bandung. Instruments of this research are six questions of written test and interview guidelines. Highest achievement at the whole sub indicators is the high ability student’s group. Overall, the student’s critical thinking skill achievement on factors affecting solubility’s learning with discovery-inquiry is good.